Australian Weightlifting Federation - High Performance Management (2008)
2009 AWF Calendar & High Performance Qualifying Total & Periods Gold Medal Incentive Program AJCGS Selection Criteria High Performance Program update, 17 July 2008 2008 Oceania Championships Report HP update, 20 Feb. 08 HP update - ASC Presentation 2008 AWF Team Officials - International Assignments Criteria ASC High Performance Review Athlete Selection Policy Team Official Policy Coach Selection Policy